Children’s Behavior toward Tooth Extraction: Comparison of Age, Chief Complaint, Method of Anesthesia, Dental Fear and Dental Anxiety with Level of Cooperation - Anjum, Shaheen; Kareem, Owais; Ilyas, Safia; Ilyas, Muhammad; Arshad, Muhammad Arqam; Ijaz, Bushra (Pakistan Journal of Medical & Health Sciences, 2022)
ABSTRACT Aim: To compare children’s behavior toward tooth extraction taking into account their gender, age, chief complaint, method of anesthesia, presence of dental fear and dental anxiety. Methodology: This cross sectional descriptive study was conducted at the Department of Maxillofacial Surgery, Nishtar Institute of Dentistry, Multan, Pakistan, from June 2021 to November 2021. The Wright’s Clinical Classification and Children’s Fear Survey Schedule Dental Subscale (CFSS-DS) were used respectively to assess the degree of cooperation and presence of dental fear anxiety (DFA) toward tooth extraction. Data was analyzed using SPSS 22. Results: Female children 167 (65%), age group of 7-8 years 83(98%), children presented with loose tooth 120 (66%), children received Inj. lignocaine 2%, 152 (70%) and children diagnosed with dental fear and anxiety 406(82%) showed uncooperative behavior toward tooth extraction. Chi squared test showed that gender (p=.01), age (p=.01), chief complaint (p=.04), method of anesthesia (p=.01), dental fear and anxiety (p=.01) were significantly associated with children’s level of cooperation toward tooth extraction procedure. Conclusion: Invasive procedure like tooth extraction brought out negative behavior hampering level of cooperation in pediatric dental treatments.